Application of Rice Husk Silica Ash Activated using NH4OH to Reduce Calcium Ion (Ca2+) Levels in Brackish Water - L. Harimu; Mutmainnah; Dahlan; W. O. Mulyana; E. C. Mandasar; I W. Sutapa; A. Kamari (Faculty Mathematics and Natural Sciences, Halu Oleo University, 2025)
A study was conducted to investigate the efficacy of NH4OH-activated rice husk ash silica in mitigating calcium ion (Ca²⁺) concentrations in brackish water. The primary objective of this research was to evaluate the adsorption capacity of NH4OH-activated rice husk ash silica for Ca²⁺ ions dissolved in brackish water. The experimental methodology employed various adsorption parameters, including pH levels (5, 6, 7, 7.5, 8, 9), adsorbent masses (0.01, 0.025, 0.05, 0.1, 0.2 g), contact times (15, 30, 45, 60, 75 minutes), and concentration levels (25, 50, 75, 100 ppm) for Ca²⁺ ions. The findings indicated that optimal adsorption occurred at an adsorbent mass of 0.025 grams, a pH of 7.5, a contact time of 30 minutes, and a concentration of 50 ppm, resulting in an adsorption capacity of 67.2 mg/g. Furthermore, under optimal conditions, the application of activated rice husk ash silica as an adsorbent in brackish water demonstrated an NH4OH adsorption capacity of 40 mg/g, with a brackish water concentration of 40 mg/g. Therefore, it can be concluded that NH4OH-activated rice husk ash silica is a viable adsorbent for reducing calcium ion (Ca²⁺) levels in brackish water.